PENDAMPINGAN KELAS IBU HAMIL DI KELURAHAN BANDARHARJO DAN KELURAHAN DADAPSARI, SEMARANG - Indri Astuti Purwanti; Nuke Devi Indrawati; Arief Tajally Adhiatma (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background. The city of Semarang was ranked third highest in terms of the number of maternal mortality cases in 2015. The work area of Bandarharjo Puskesmas has the highest number of deaths among other areas in Semarang City and all pregnant women in this region were classified as high risk during the year. The cause is indifference to pregnancy examination. This is indicated by the low attendance of pregnant class. Objective. The purpose of this activity is to increase the presence of pregnant classes and to increase awareness of pregnancy and high risk pregnancy outcomes. Method. The method used is the empowerment and mentoring of partners, as well as health education for pregnant women (target). Results. The attendance and care of the pregnant class of Bandarharjo Urban Village is still ongoing while the Dadapsari Village has increased.Keywords: class of pregnant women, concern for pregnancy examination.